Analysis of Amenities in Increasing Tourism Revenue at Curug Cigentis Karawang - Sandi, Santi Pertiwi Hari; Mulyadi, Dedi (West Science Business and Management, 2023)
This research aims to find out about the state of amenities at one of the tourist attractions in the southern area of Karawang Regency, namely Curug Cigentis which is at the foot of Mount Sanggabuana. Amenities consist of health hygiene facilities, security, communications, amusement rides, accommodation, souvenir shop, prayer room, parking area, toilet, restaurant. From several amenity components in this tour, can we determine changes in tourist attractions. This research uses a qualitative descriptive method where data collection is carried out using interviews with 82 visitors. Business managers and owners at the Curug Cigentis tourist location, and secondary and primary data needed in this research. The results of this research show that the amenities owned and prepared by the management of Curug Cigentis really help tourist activities. Because there is cleanliness, health, security, communication, amusement rides, souvenir shops, prayer rooms, parking lots, toilets, restaurants. However, there are differences in rates for car parking fees, you have to add costs for communication availability by purchasing WiFi, and paying for the swimming pool at the Curug Cigentis tourist location. Meanwhile, MCK is available for free and for food and drink prices there is equal price, if you want to buy it at any stall along Curug Cigentis the price is the same. Good handling of amenities will increase income because visitors will want to visit the tourist location because they feel that supporting facilities are available, providing a sense of security and comfort.